Implementasi Pembelajaran Inovatif (Studi Penerapan Metode Perapat Di Sekolah Dasar Negeri Mojorejo 1 Kota Batu) - Novia Mazazi Manurung; Prilia Rahmadina; Sugiarti Sugiarti (UMSU, 2023)
This research is motivated by students' incomplete understanding of the distribution material, so it requires improvement in learning. There are many ways to solve division problems, one of which is using the fast distribution method (Perapat). The purpose of this study was to improve the mathematics learning outcomes of fourth grade students in solving division problems using the close method. This research method uses classroom action research consisting of 2 cycles, with the stages of planning, action, observation and reflection. There is an increase in student learning outcomes from the pre-cycle stage, cycle I to cycle II. In pre-cycle, the average learning result is 50.9 with a completeness percentage of 33.3%. Cycle I was given the action of applying the methodattachment,obtain the average learning outcome is 80.4, and the percentage of completeness is 63.0%. In cycle II, the average learning outcomes were an increase in the average learning outcomes of 88.4 and the percentage of completeness was 88.9%. It was concluded that the application of the material distribution meeting method could improve the learning outcomes of fourth grade students at SDN Mojorejo 1 Kota Batu.